Magnetoelectric nano composite film as well as preparation method and application thereof

The nanocomposite film was prepared by a three-target magnetron co-sputtering process, and uniformly distributed Co nanoparticles in the MgF2 ceramic matrix, solving the problems of low magnetization and poor magnetoelectric properties of existing materials, and achieving nanocomposite films with high magnetization and strong magnetoelectric coupling properties.

CN119615084APending Publication Date: 2025-03-14HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411619527.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing magnetoelectric nanocomposites have low magnetization and poor magnetoelectric properties, making it difficult to flexibly regulate the synergistic effects between various material components.

Method used

Nanocomposite films were prepared by three-target magnetron co-sputtering process, and nanocomposite structures with sub-nano-scale spacing were formed by uniformly distributing magnetic Co nanoparticles in the MgF2 ceramic matrix.

Benefits of technology

The magnetization strength and magnetoelectric coupling performance of the film are significantly improved, and efficient magnetoelectric response is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615084A_ABST
    Figure CN119615084A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetoelectric nano-composite film and a preparation method and application thereof, a nano-composite film material comprises a magnetic phase and an insulating ceramic phase, the magnetic phase comprises magnetic Co nanoparticles, the insulating ceramic phase comprises a MgF2 ceramic matrix, the magnetic Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix, and the spacing between adjacent magnetic Co nanoparticles is in a sub-nanometer level; the three-target sputtering process is adopted, the deposition rate of the film is effectively increased, the Co nano-particles are evenly distributed in the MgF2 ceramic matrix, the distance between the nano-particles is in the sub-nanometer level, the nano-composite structure with the tunneling magnetoelectric effect is formed, and the obtained film is high in magnetization intensity and high in magnetoelectric coupling performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of magnetoelectric functional materials technology, and in particular to a magnetoelectric nanocomposite thin film, its preparation method and application. Background Technology

[0002] The magnetoelectric effect, which allows for the active modulation of the electrical properties of materials through an applied magnetic field, has attracted widespread attention. However, due to the scarcity of single-phase magnetoelectric materials and their relatively low operating temperatures, research has gradually shifted towards composite material systems. Composite materials include two-phase compounds with layered, columnar, and granular structures, achieving their magnetoelectric response through strain-mediated interaction between the piezoelectric and magnetostrictive phases, or by combining the Maxwell-Wagner-Sillars effect with the magnetoresistance effect. These heterostructures exhibit higher operating temperatures and can achieve larger magnetoelectric responses.

[0003] A novel room-temperature magnetoelectric effect, tunneling magnetoelectric (TMD), has been observed in particulate nanocomposites. This effect primarily works through the interaction between the matrix and the particles, causing charge carriers to spin-oscillate and induce polarization between adjacent particles. To enhance this magnetoelectric response, researchers have employed strategies such as alloying and the fabrication of heterostructures or monolayer films. Specifically, alloying replaces cobalt with an iron-cobalt binary alloy, which, due to its higher spin polarizability, enhances the spin-dependent oscillation of charge carriers between nanoparticles, resulting in a stronger tunneling effect. The heterostructure strategy optimizes the interaction between particles and the tunneling effect; the excellent thermal stability and electrical insulation of the insulating matrix enhance the magnetoelectric response and maintain its stability over a wide frequency range. The monolayer film strategy reduces the thickness of the nanoparticle structure to the monolayer limit, effectively reducing electron scattering and improving magnetoelectric properties. However, these methods struggle to flexibly control the synergistic effects between various material components, resulting in materials with low magnetization and poor magnetoelectric performance.

[0004] Therefore, there is a need to provide a magnetoelectric nanocomposite thin film with high magnetization and good magnetoelectric properties. Summary of the Invention

[0005] In view of this, this application provides a magnetoelectric nanocomposite thin film, its preparation method and application, to solve the problem of how to improve the magnetization and magnetoelectric properties of magnetoelectric nanocomposite thin films.

[0006] To achieve the above technical objectives, this application adopts the following technical solution: In a first aspect, this application provides a nanocomposite thin film material comprising a magnetic phase and an insulating ceramic phase. The magnetic phase comprises magnetic Co nanoparticles, and the insulating ceramic phase comprises a MgF2 ceramic matrix. The magnetic Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix, and the spacing between adjacent magnetic Co nanoparticles is at the sub-nanometer level.

[0007] Preferably, the general chemical formula of the nanocomposite thin film material is Co. x (MgF2) 1−x , where 0.12≤x≤0.23.

[0008] Preferably, the magnetic Co nanoparticles have a particle size of 2-5 nm and the spacing between adjacent magnetic Co nanoparticles is 0.2-0.5 nm.

[0009] Secondly, this application provides a magnetoelectric nanocomposite thin film containing a nanocomposite thin film material.

[0010] Thirdly, this application provides a method for preparing a magnetoelectric nanocomposite thin film, comprising the following steps: S1. Obtain the substrate; S2. Nanocomposite thin films are prepared on the substrate surface by a three-target magnetron co-sputtering process; S3. Press the electrode material onto the surface of the nanocomposite film to obtain the magnetoelectric nanocomposite film.

[0011] Preferably, in step S2, the specific operation of preparing a nanocomposite thin film on the substrate surface by the three-target magnetron co-sputtering process is as follows: a Co sputtering target, a first MgF2 sputtering target, and a second MgF2 sputtering target are simultaneously sputtered onto the substrate surface, and after deposition, a nanocomposite thin film is obtained.

[0012] Preferably, in the three-target magnetron co-sputtering process, the background vacuum level is: 7-9 × 10⁻⁶ -5 The target distance is 50-60 cm, the working gas is argon, the working gas flow rate is 10-20 sccm, and the working pressure is 0.25-0.5 Pa; the sputtering power of the first MgF2 sputtering target is 200-250 W, the sputtering power of the second MgF2 sputtering target is 200-250 W, and the sputtering power of the Co sputtering target is 90-130 W.

[0013] Preferably, the substrate includes one or more of Si substrates, Si / SiO2 / Ti / Pt composite substrates.

[0014] Preferably, the electrode material includes a conductive indium plate.

[0015] Fourthly, this application provides an application of a magnetoelectric nanocomposite thin film in a magnetic sensor or impedance-tunable device.

[0016] The beneficial effects of this application are as follows: This application adopts a three-target sputtering process, which effectively improves the deposition rate of the thin film (1.6 times higher than the dual-target sputtering process), so that Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix and the spacing between nanoparticles is at the sub-nanometer level, forming a nanocomposite structure with tunneling magnetoelectric effect. The resulting thin film has high magnetization and strong magnetoelectric coupling performance. Attached Figure Description

[0017] Figure 1 This is a schematic diagram of two deposition methods: LRD and HRD. Figure 2 Comparison of the relationship between Co target sputtering power and deposition rate for magnetoelectric nanocomposite thin films prepared by different methods; Figure 3 The cross-sectional structure of Co-MgF2 prepared in Example 1. Detailed Implementation

[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0019] This application provides a nanocomposite thin film material comprising a magnetic phase and an insulating ceramic phase. The magnetic phase includes magnetic Co nanoparticles, and the insulating ceramic phase includes a MgF2 ceramic matrix. The magnetic Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix, and the spacing between adjacent magnetic Co nanoparticles is at the sub-nanometer level.

[0020] In this application, both the magnetic phase and the insulating ceramic phase are crystalline structures, and the spacing between nanoparticles is at the sub-nanometer level, ensuring the effective realization of the tunneling magnetoelectric effect. Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix, forming a nanocomposite structure with tunneling magnetoelectric effect, which is beneficial to the improvement of magnetoelectric performance.

[0021] The general chemical formula of the nanocomposite thin film material in this application is Co. x (MgF2) 1−x Where 0.12≤x≤0.23, and x represents the molar content of Co.

[0022] In some embodiments, the magnetic Co nanoparticles have a particle size of 2-5 nm; the spacing between adjacent magnetic Co nanoparticles is 0.2-0.5 nm.

[0023] This application provides a magnetoelectric nanocomposite thin film containing a nanocomposite thin film material.

[0024] This application provides a method for preparing a magnetoelectric nanocomposite thin film, comprising the following steps: S1. Obtain the substrate; S2. Nanocomposite thin films are prepared on the substrate surface by a three-target magnetron co-sputtering process; S3. Press the electrode material onto the surface of the nanocomposite film to obtain the magnetoelectric nanocomposite film.

[0025] This application employs a three-target radio frequency magnetron sputtering technique to prepare Co-MgF2 composite nanoparticle thin films. Compared with traditional dual-target magnetron sputtering, this application adds a MgF2 target during film preparation, significantly improving the deposition rate, which in turn benefits the distribution of magnetic particles and enhances magnetic properties.

[0026] like Figure 1 As shown, a comparison is made between the classic low-rate magnetron sputtering deposition (LRD) method and the high-rate magnetron sputtering deposition (HRD) method of this application. The left figure shows the LRD method, which uses two sputtering targets: MgF2 and Co, and deposits onto the substrate at a low rate. The right figure shows the HRD method, which adds a third MgF2 sputtering target. By sputtering three targets simultaneously, a higher deposition rate can be achieved, which is beneficial to the distribution of magnetic particles and the improvement of magnetic properties.

[0027] In some embodiments, in step S2, the specific operation of preparing a nanocomposite thin film on the substrate surface by a three-target magnetron co-sputtering process is as follows: a Co sputtering target, a first MgF2 sputtering target, and a second MgF2 sputtering target are simultaneously sputtered onto the substrate surface, and after deposition, a nanocomposite thin film is obtained.

[0028] In some embodiments, the background vacuum level in the three-target magnetron co-sputtering process is 7-9 × 10⁻⁶. -5 The target-substrate distance was 50-60 cm, the working gas was argon, the working gas flow rate was 10-20 sccm, and the working pressure was 0.25-0.5 Pa. The sputtering power of the first MgF2 sputtering target was 200-250 W, the sputtering power of the second MgF2 sputtering target was 200-250 W, and the sputtering power of the Co sputtering target was 90-130 W. By adjusting the sputtering power of the Co target, the content of Co nanoparticles in the film could be adjusted, thereby controlling the magnetic properties of the material.

[0029] In some embodiments, the substrate includes one or more of a Si substrate and a Si / SiO2 / Ti / Pt composite substrate. The Si / SiO2 / Ti / Pt composite substrate is prepared using a multilayer deposition technique to ensure excellent adhesion and electrical properties of the thin film. The preparation method of the Si / SiO2 / Ti / Pt composite substrate is as follows: a SiO2 barrier layer is prepared on the Si substrate by high-temperature oxidation; subsequently, a 50 nm Ti layer is deposited as an adhesion layer using thermal evaporation; finally, a 100 nm Pt layer is deposited on the Ti layer as the bottom electrode.

[0030] In some embodiments, the electrode material includes a conductive indium plate.

[0031] The specific operation of step S3 is as follows: cut the conductive metal indium In plate into 1 mm long slices and press them onto the surface of the nanocomposite film as a circular top electrode with a diameter of 1 mm.

[0032] This application provides an application of a magnetoelectric nanocomposite thin film in a magnetic sensor or impedance-tunable device.

[0033] The following specific embodiments further illustrate this solution.

[0034] Examples 1-5 A method for preparing a magnetoelectric nanocomposite thin film includes the following steps: S1. A SiO2 barrier layer is prepared on a Si substrate by high-temperature oxidation. Then, a 50 nm Ti layer is deposited as an adhesion layer using thermal evaporation. Finally, a 100 nm Pt layer is deposited on the Ti layer as a bottom electrode to obtain a Si / SiO2 / Ti / Pt composite substrate as a substrate. S2. Using a three-target magnetron co-sputtering process, a Co sputtering target (target A), a first MgF2 sputtering target (target B), and a second MgF2 sputtering target (target C) are simultaneously sputtered onto the substrate surface. After deposition, a nanocomposite thin film is obtained; wherein the base vacuum is 9 × 10⁻⁶. - 5 Pa, target-substrate distance 50 cm, working gas is argon (Ar) and working pressure is 0.25 Pa, the dual sputtering power of the first MgF2 sputtering target and the second MgF2 sputtering target is 250 W, corresponding to Examples 1-5, the sputtering power of Co is 90 W, 100 W, 110 W, 120 W and 130 W respectively.

[0035] S3. Cut conductive indium (In) strips into 1 mm long pieces and press them onto the surface of the nanocomposite film to form a circular top electrode with a diameter of 1 mm, thus obtaining the magnetoelectric nanocomposite film.

[0036] Comparative Examples 1-5 A method for preparing a magnetoelectric nanocomposite thin film includes the following steps: S1. A SiO2 barrier layer is prepared on a Si substrate by high-temperature oxidation. Then, a 50 nm Ti layer is deposited as an adhesion layer using thermal evaporation. Finally, a 100 nm Pt layer is deposited on the Ti layer as a bottom electrode to obtain a Si / SiO2 / Ti / Pt composite substrate as a substrate. S2. Using a dual-target magnetron co-sputtering process, a Co sputtering target (target A) and a first MgF2 sputtering target (target B) are simultaneously sputtered onto the substrate surface. After deposition, a nanocomposite thin film is obtained; wherein the base vacuum is 9 × 10⁻⁶. -5 Pa, target distance 50 cm, working gas is argon (Ar) and working pressure is 0.25 Pa, sputtering power of the first MgF2 sputtering target is 250 W, corresponding to ratios 1-5, sputtering power of Co is 90 W, 100 W, 110 W, 120 W and 130 W respectively.

[0037] S3. Cut conductive indium (In) strips into 1 mm long pieces and press them onto the surface of the nanocomposite film to form a circular top electrode with a diameter of 1 mm, thus obtaining the magnetoelectric nanocomposite film.

[0038] Testing and Evaluation The relationship between Co target sputtering power and deposition rate was compared between the HRD method in Examples 1-5 and the LRD method in Comparative Examples 1-5. The results are as follows: Figure 2 As shown.

[0039] The cross-sectional structure of the magnetoelectric nanocomposite thin film obtained in Example 1 was tested using transmission electron microscopy (TEM), and the results are as follows: Figure 3 As shown.

[0040] Depend on Figure 2 It can be seen that the HRD method has a higher deposition rate, and the Co-MgF2 thin film obtained by the HRD method has a uniform distribution of nanoparticles. Figure 3 The transmission electron microscope (TEM) images clearly show the structure of the Co nanoparticles in this application. The Co nanoparticles have a diameter of about 2-5 nm and are uniformly dispersed in the MgF2 matrix. The spacing between the Co nanoparticles is 0.2-0.5 nm.

[0041] The composition of the magnetoelectric nanocomposite films obtained in Examples 1-5 and Comparative Examples 1-5 was determined, and the corresponding magnetization and magnetic dielectric changes were tested. The magnetoelectric change rate was defined as the rate of change of dielectric constant of the film before and after the application of a magnetic field. Before measurement, an impedance analyzer (Keysight, E4990A) was used to calibrate the equipment under "short circuit" and "open circuit" conditions to ensure the accuracy of the measurement results. The magnetoelectric change rate was calculated using the formula: Magnetoelectric change rate = (ε'H - ε'0) / ε'0 × 100%. The results are shown in Table 1.

[0042] Table 1 Test Results

[0043] The results in Table 1 show that the films prepared by the HRD method exhibit higher magnetization as the Co content increases, proving that high-speed deposition is beneficial to the distribution of magnetic particles and the improvement of magnetic properties. With the increase of Co content, the HRD films exhibit higher magnetoelectric change rate, especially at higher Co contents, indicating that this method has significant advantages in enhancing the magnetoelectric properties of films.

[0044] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A nanocomposite film material, characterized in that: It comprises a magnetic phase and an insulating ceramic phase. The magnetic phase comprises magnetic Co nanoparticles. The insulating ceramic phase comprises a MgF2 ceramic matrix. The magnetic Co nanoparticles are uniformly distributed in the MgF2 ceramic matrix. The distance between adjacent magnetic Co nanoparticles is sub-nanometer.

2. The nanocomposite film material according to claim 1, characterized in that: Its chemical formula is Co x (MgF2) 1−x , where 0.12≤x≤0.

23.

3. The nanocomposite film material according to claim 1, characterized in that: The particle size of the magnetic Co nanoparticles is 2-5 nm; the distance between adjacent magnetic Co nanoparticles is 0.2-0.5 nm.

4. A magnetoelectric nanocomposite film comprising the nanocomposite film material according to any one of claims 1 to 3.

5. A method for preparing a magnetoelectric nanocomposite film as claimed in claim 4, characterized in that: The following steps are involved: S1. Obtain a substrate; S2. Preparing a nanocomposite film on the surface of the substrate by a three-target magnetron co-sputtering process; S3. Pressing the electrode material onto the surface of the nanocomposite film to obtain the magnetoelectric nanocomposite film.

6. The preparation method according to claim 5, characterized in that: In step S2, the specific operation of preparing the nano-composite film on the surface of the substrate by a three-target magnetron co-sputtering process is: sputtering a Co sputtering target, a first MgF2 sputtering target, and a second MgF2 sputtering target simultaneously on the surface of the substrate, and after deposition, the nano-composite film is obtained.

7. The preparation method according to claim 6, characterized in that In the three-target magnetron co-sputtering process, the background vacuum degree is: 7-9×10 -5 Pa, the target-substrate distance is 50-60 cm, the working gas is argon, the working gas flow rate is 10-20sccm, and the working gas pressure is 0.25-0.5Pa; the sputtering power of the first MgF2 sputtering target is 200-250W, the sputtering power of the second MgF2 sputtering target is 200-250W, and the sputtering power of the Co sputtering target is 90-130 W.

8. The preparation method according to claim 5, characterized in that: The substrate includes one or more of a Si substrate and a Si / SiO2 / Ti / Pt composite substrate.

9. The preparation method according to claim 5, characterized in that: The electrode material includes a conductive metal indium plate.

10. Use of the magnetoelectric nanocomposite film obtained by the preparation method according to any one of claims 5 to 9 in a magnetic sensor or an impedance adjustable device.